Chronic Stress-Induced Depression and Anxiety Priming Modulated by Gut-Brain-Axis Immunity. (14th June 2022) - Pasinetti, Giulio; Westfall, Susan
Abstract: Objectives: Chronic stress manifests as depressive- and anxiety-like behavior while recurrent stress elicits disproportionate psychiatric responses linked to stress-induced immunological priming. The gut-brain-microbiota-axis is a promising therapeutic target for stress-induced behavioral impairments as it simultaneously modulates peripheral and brain immunological landscapes. Methods: In this study, a combination of probiotics and prebiotics (i.e., synbiotic) promoted behavioral resilience to chronic and recurrent stress by normalizing gut microbiota populations and promoting regulatory T cell (Treg) expansion through modulation of ileal innate lymphoid cell (ILC)3 activity, an impact reflecting behavioral responses better than limbic brain region neuroinflammation. Results: A multivariate machine learning model predicted a cross-tissue immunological signature of stress-induced behavioral impairment where ileal Treg/T helper17 cell ratio associated to hippocampal chemotactic chemokine and prefrontal cortex IL‐1 release in the context of stress-induced behavioral deficits. Conclusions: In conclusion, stress-induced behavioral impairments depend on the gut-brain microbiota-axis and through ileal immune regulation, synbiotics attenuate the associated depressive- and anxiety-like behavior. Funding Sources: The study was supported by grant number P50 AT008661-01 and U19 AT010835 from the NCCIH and the ODS.